Patients Receiving Integrative Medicine Effectiveness Registry (PRIMIER) of the BraveNet practice-based research network: study protocol. Issue 1 (December 2015) - Dusek, Jeffery; Abrams, Donald; Roberts, Rhonda; Griffin, Kristen; Trebesch, Desiree; Dolor, Rowena; Wolever, Ruth; McKee, M.; Kligler, Benjamin
Abstract Background Integrative medicine (IM) provides patient-centered care and addresses the full range of physical, emotional, mental, social, spiritual, and environmental influences that affect a person's health. IM is a "whole systems" approach that employs multiple modalities as opposed to an isolated complementary therapy. Thus, studying outcomes of IM is more challenging than evaluating an isolated intervention. Practice-based research networks (PBRNs) allow for clinicians/investigators at multiple diverse sites using common methodology to pool their data, increase participant sample size and increase generalizability of results. To conduct real-world, practice-based research, the Bravewell Collaborative founded BraveNet in 2007 as the first national integrative medicine PBRN. Methods and design Patients Receiving Integrative Medicine Effectiveness Registry (PRIMIER) is a prospective, non-randomized, observational evaluation conducted at fourteen clinical sites. Participants receive a non-standardized, personalized, multimodal IM approach for various medical conditions. Using the REDCap electronic platform, an anticipated 10, 000 study participants will complete patient-reported outcome measures including Patient Reported Outcomes Measurement Information System (PROMIS)-29, Perceived Stress Scale-4, and the Patient Activation Measure at baseline, 2, 4, 6, 12, 18 and 24 months. Extractions from participants' electronic health records include IM services received, as well as ICD diagnostic codes, and CPT billing codes associated with each IM visit. Repeated-measures analyses will be performed on data to assess change from baseline through 24 months with planned subgroup analyses to include specific clinical population and specific IM intervention or combinations. Discussion As the PRIMIER registry grows, we anticipate that our results would provide an indication of the promise of PBRN research efforts in IM. Analyses will incorporate a large sample of participants and an expected 10-year observation period and will provide the ability to evaluate the effect of IM on outcomes for specific clinical populations and specific IM interventions or combinations. As such, PRIMIER will serve as a national platform for future evaluations of IM best practices. Trial registration Clinical Trials.govNCT01754038